Short- and Long-Run Business Conditions and Expected Returns - Liu, Qi; Tao, Libin; Wu, Weixing; Yu, Jianfeng (Management Science, 2017)
Numerous studies argue that the market risk premium is associated with expected economic conditions and show that proxies for expected business conditions indeed predict aggregate market returns. By directly estimating short- and long-run expected economic growth, we show that short-run expected economic growth is negatively related to future returns, whereas long-run expected economic growth is positively related to aggregate market returns. In addition, our findings indicate that the risk premium has both high- and low-frequency fluctuations and highlight the importance of distinguishing short- and long-run economic growth in macro-asset pricing models. This paper was accepted by Neng Wang, finance.